Dermal Microvascular Units in Domestic Pigs (Sus scrofa domestica): Role as Transdermal Passive Immune Channels - Meng, Xiangfei; Zhu, Zhaoxuan; Ahmed, Nisar; Ma, Qianhui; Wang, Qi; Deng, Bihua; Chen, Qiusheng; Lu, Yu; Yang, Ping (Frontiers in Veterinary Science, 2022)
The dermal microvascular unit (DMU) is a perivascular functional unit in the dermis. It is composed of microvascular and capillary lymphatics surrounded by immune cells. In this study, jet needle-free injection system was used to injected biocompatible carbon nanoparticles into the cervical skin of domestic pigs (Sus scrofa domestica) and assessed the morphological distribution of DMUs by hematoxylin erythrosine staining, immunohistochemistry (IHC), and transmission electron microscopy (TEM), and TEM was also used to observe the ultrastructural changes of DMUs after jet needle-free injection. Following our study, we identified DMUs in the dermis stratum papillare and similar structures in the dermis stratum reticulare, but the aggregation of CD68+ and CD1a+ cells in the dermis stratum papillare of DMUs by IHC confirmed that DMUs act as reservoirs of dermal immune cells, while similar structures in the dermis stratum reticulare should not be considered as DMUs. Ultrastructure of DMUs was revealed by TEM. Marvelous changes were found following xenobiotics attack, including the rearrangement of endothelial cells and pericytes, and the reactivity of immune cells. Novel interstitial cell telocyte (TC) was also identified around the microvasculature, which may have been previously known as the veil cell. Our results successfully identified the distribution of DMUs in the skin of domestic pigs, which might act as reservoirs of immune cells in the skin and play a role in immune surveillance and immune defense.